2017
DOI: 10.3233/jad-170168
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Tau Oligomers Induce Invasion of Endogenous Tau into the Somatodendritic Compartment and Axonal Transport Dysfunction

Abstract: Aggregates composed of the microtubule associated protein, tau, are a hallmark of Alzheimer’s disease and non-Alzheimer’s tauopathies. Extracellular tau can induce the accumulation and aggregation of intracellular tau, and tau pathology can be transmitted along neural networks over time. There are six splice variants of central nervous system tau, and various oligomeric and fibrillar forms are associated with neurodegeneration in vivo. The particular extracellular forms of tau capable of transferring tau patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 59 publications
2
49
0
Order By: Relevance
“…Seeds of trans-synaptically transferred tau would make first contact with post-synaptic tau within receiving neurons, raising the intriguing concept that post-synaptic tau is the primary target for prion-like spreading of tau pathology, including possibly localized oligomerization of tau. Consistent with this idea, exposure to extracellular tau promoted recruitment of endogenous tau into dendrites (Swanson et al, 2017). Other post-synaptic processes may further contribute to trans-synaptic spread of tau pathology; for example, neuronal activity was shown to promote spread of tau pathology in vivo and in vitro (Calafate et al, 2015;Wu et al, 2016).…”
Section: Post-translational Modifications Of Tau In Post-synaptic Sigmentioning
confidence: 74%
See 1 more Smart Citation
“…Seeds of trans-synaptically transferred tau would make first contact with post-synaptic tau within receiving neurons, raising the intriguing concept that post-synaptic tau is the primary target for prion-like spreading of tau pathology, including possibly localized oligomerization of tau. Consistent with this idea, exposure to extracellular tau promoted recruitment of endogenous tau into dendrites (Swanson et al, 2017). Other post-synaptic processes may further contribute to trans-synaptic spread of tau pathology; for example, neuronal activity was shown to promote spread of tau pathology in vivo and in vitro (Calafate et al, 2015;Wu et al, 2016).…”
Section: Post-translational Modifications Of Tau In Post-synaptic Sigmentioning
confidence: 74%
“…Specifically, this study used expression of a dominant-negative tau variant and tau depletion in mice to reveal how endogenous tau mediates post-synaptic signals in Ab toxicity. Subsequent studies confirmed that endogenous tau localizes to dendrites and post-synapses in rodent neurons, using immune-labeling, synaptosomal fractionation, and ultrastructural analysis approaches (Ittner et al, 2010(Ittner et al, , 2016Kimura et al, 2013;Mondragó n-Rodríguez et al, 2012;Swanson et al, 2017;Zempel et al, 2013). Furthermore, mice genetically engineered to express endogenous tau with a C-terminally fused mEOS2 fluorescent reporter showed that endogenous murine tau localizes to dendritic spines (Xia et al, 2016).…”
Section: Regulatory Pathways Of Dendritic/post-synaptic Tau Localizationmentioning
confidence: 81%
“…The dependence of axons on proper anterograde and retrograde AT is evident because mutations in selected conventional kinesins or cytoplasmic dynein subunits suffice to promote dying-back degeneration of neurons (Morfini et al, 2009 ). Providing an explanation for the axonal degeneration phenotype observed in tauopathies, multiple independent studies documented deficits in AT triggered by pathogenic forms of tau, including oligomeric tau (Higuchi et al, 2005 ; Gotz et al, 2006 ; Cox et al, 2016 ; Swanson et al, 2017 ). Several mechanisms are proposed to mediate this toxic effect.…”
Section: Pathogenic Mechanisms Linking Abnormal Tau To Axonopathymentioning
confidence: 99%
“…In this study, we produced all six recombinant human tau isoforms that are as aggregationcompetent to form oligomers and mature filaments as those in AD and other tauopathies (Swanson et al, 2017). We dissected the key segments in tau isoforms contributing to their aggregation.…”
Section: Introductionmentioning
confidence: 99%